2019
DOI: 10.1007/s13762-019-02373-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hazards of the moassel consumed in Baghdad/Iraq using NaI(Tl) gamma spectroscopy

Abstract: Smoking narghile has become a common occurrence among young Iraqi people since several years ago, moassel is the name given to the tobacco dentifrice smoked by Iraqi people, and it consists of tobacco, honey, glycerin and flavors. Tobacco which is the main component of the moassel has a little amount of some radioisotopes, but nevertheless few studies have addressed the radioactivity and the potential risks in moassel. Samples of the most common moassel types consumed in Iraq are collected from the markets, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…ICRP, 2007 reported that the mean effective dose for the public worldwide is 0.48 mSv [ 42 , 43 ]. Calculated annual effective doses in several locations are higher than that value and all data are below the acceptable limit of 1 mSv for the public [ 44 , 45 ]. Table 3 recounts the estimated ELCR on public according to ICRP & BEIR recommended guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…ICRP, 2007 reported that the mean effective dose for the public worldwide is 0.48 mSv [ 42 , 43 ]. Calculated annual effective doses in several locations are higher than that value and all data are below the acceptable limit of 1 mSv for the public [ 44 , 45 ]. Table 3 recounts the estimated ELCR on public according to ICRP & BEIR recommended guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…The rate (D γ ) in the air at 1 m above the ground surface is calculated per unit of specific activity (in 1 Bq kg −1 Another radiological index is the annual effective dose equivalent (AEDE), which depends on the absorbed gamma dose (D) in nGy h −1 and the conversion constant (0.7 Sv G −1 ) in the outdoors (in the air) from the absorbed dose in the air to the effective dose. 0.2 is the outdoor occupancy factor, and 8760 h y −1 is the hours in 1 year [17,18]…”
Section: Radiation Hazard Indicesmentioning
confidence: 99%
“…The system has a digital multichannel analyzer (bright multichannel SPEC model bMCA) of 4096 channels and 695V operation voltage. The time of examination used were 24hr (86400 s) [17,18].…”
Section: Nai (Tl) Spectroscopymentioning
confidence: 99%